2003
DOI: 10.3109/713745178
|View full text |Cite
|
Sign up to set email alerts
|

Proteinous Amino Acids in Muscle Cytosol of Rats' Heart After Exercise and Hypoxia

Abstract: Levels of 19 proteinous amino acids and of total free amino acids were assayed by gas-liquid chromatography in cytosols of rat atrial and ventricular heart muscle cardiomyocytes. These amino acids were assayed after the rats had been exposed to either exercise (swimming) or hypoxia (hypobaric pressure of 686 hectoPascals). Out of the total free amino acids levels of arginine, glutamine and cysteine in atrial and ventricular cardiac muscle cytosols of control rats were the highest of all amino acids assayed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Propranolol and pentylenetetrazol decreased the 91 level of cysteine. We confirmed these results in another study (Gabrys et al 2003).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Propranolol and pentylenetetrazol decreased the 91 level of cysteine. We confirmed these results in another study (Gabrys et al 2003).…”
Section: Introductionsupporting
confidence: 93%
“…It was demonstrated that both physical stress and the three drugs, affected the levels of proteinous amino acids, mostly cysteine, arginine, histidine, isoleucine, alanine and tyrosine (Gabrys et al 2003(Gabrys et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Similar decrease in ventricular L-arginine was observed in rats after hypoxia stress (Gabrys et al 2003) It is suggested that administration of these drugs, and hypoxia, enhance the release of agents such as endothelin and/or oxygen-derived free radicals, that in turn increase the production of endogenous NO and consequently decrease muscle-cytosol levels of L-arginine, its endogenous donor (Mullane et al 1987;Vane and Botting 1993). It was also suggested that NO prevents the intensive cardiac stimulation, as it is involved in the negative chronotropic effect of endothelium in the heart muscle (Zhu et al 1997).…”
Section: Discussionmentioning
confidence: 52%
“…In previous studies we have demonstrated that exercise completely abolished, while hypoxia decreased the levels of cysteine in the atrial heart muscle cytosol (Gabrys et al 2003). As exercise is a most stressful procedure, we believe that in the present study all the cysteine from the atrial cytosols turned into atriopeptins.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation